Acylcarnitines: potential implications for skeletal muscle insulin resistance. Issue 1 (23rd October 2014) - Aguer, Céline; McCoin, Colin S.; Knotts, Trina A.; Thrush, A. Brianne; Ono‐Moore, Kikumi; McPherson, Ruth; Dent, Robert; Hwang, Daniel H.; Adams, Sean H.; Harper, Mary‐Ellen
Abstract : Insulin resistance may be linked to incomplete fatty acid β‐oxidation and the subsequent increase in acylcarnitine species in different tissues including skeletal muscle. It is not known if acylcarnitines participate in muscle insulin resistance or simply reflect dysregulated metabolism. The aims of this study were to determine whether acylcarnitines can elicit muscle insulin resistance and to better understand the link between incomplete muscle fatty acid β‐oxidation, oxidative stress, inflammation, and insulin‐resistance development. Differentiated C2C12, primary mouse, and human myotubes were treated with acylcarnitines (C4:0, C14:0, C16:0) or with palmitate with or without carnitine acyltransferase inhibition by mildronate. Treatment with C4:0, C14:0, and C16:0 acylcarnitines resulted in 20–30% decrease in insulin response at the level of Akt phosphorylation and/or glucose uptake. Mildronate reversed palmitate‐induced insulin resistance concomitant with an 25% decrease in short‐chain acylcarnitine and acetylcarnitine secretion. Although proinflammatory cytokines were not affected under these conditions, oxidative stress was increased by 2–3 times by short‐ or long‐chain acylcarnitines. Acylcarnitine‐induced oxidative stress and insulin resistance were reversed by treatment with antioxidants. Results are consistent with the conclusion that incomplete muscle fatty acid β‐oxidation causes acylcarnitine accumulation and associated oxidative stress, raising the possibility that these metabolites play a role in muscle insulin resistance.—Aguer, C., McCoin, C. S., Knotts, T. A., Thrush, A. B., Ono‐Moore, K., McPherson, R., Dent, R., Hwang, D. H., Adams, S. H., Harper, M.‐E. Acylcarnitines: potential implications for skeletal muscle insulin resistance. FASEB J. 29, 336–345 (2015). www.fasebj.org